2011
DOI: 10.1002/yea.1844
|View full text |Cite
|
Sign up to set email alerts
|

Low ergosterol content in yeast adh1 mutant enhances chitin maldistribution and sensitivity to paraquat‐induced oxidative stress

Abstract: Alcohol dehydrogenases catalyse the reversible oxidation of alcohols to aldehydes or ketones, with concomitant reduction of NAD + or NADP + . Adh1p is responsible for the reduction of acetaldehyde to ethanol, while Adh2p catalyses the reverse reaction, the oxidation of ethanol to acetaldehyde. Lack of Adh1p shifts the cellular redox balance towards excess NADH/NADPH and acetaldehyde, while absence of Adh2p does the opposite. Yeast mutant adh1 had a slow growth rate, whereas adh2 grew like the isogenic wild-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 55 publications
2
10
1
Order By: Relevance
“…DHE-exposed M. perniciosa hyphae had shown a similar profile when subjected to a free radical-generating chemical treatment. Marisco et al [49] had shown similar results in the eukaryotic model in S. cerevisiae (yeast) using H 2 O 2 as pro oxidant. There is evidence for the role of endogenous ROS as a causative agent in mutagenesis and as a significant contributor in the mutational burden in microbes during periods of oxidative stress in which this response may be related to cytotoxicity [50].…”
Section: Discussionmentioning
confidence: 68%
“…DHE-exposed M. perniciosa hyphae had shown a similar profile when subjected to a free radical-generating chemical treatment. Marisco et al [49] had shown similar results in the eukaryotic model in S. cerevisiae (yeast) using H 2 O 2 as pro oxidant. There is evidence for the role of endogenous ROS as a causative agent in mutagenesis and as a significant contributor in the mutational burden in microbes during periods of oxidative stress in which this response may be related to cytotoxicity [50].…”
Section: Discussionmentioning
confidence: 68%
“…In addition, as the mutant showed an increased osmo‐sensitivity, paraquat and H 2 O 2 may penetrate the plasma membrane of the mutant more easily than that of the wild‐type, resulting in increased sensitivity of the mutant to these stress agents. In S. cerevisiae and C. albicans , the mutants with impaired ergosterol synthesis and a low content of ergosterol exhibited enhanced synthesis of chitin and abnormal distribution of chitin in their cell walls (Chiew et al ., ; Marisco et al ., ; Schmidt et al ., ). In this study, we found that the cell wall of ΔFgErg4‐2 was more resistant to the mixture of cellulase, lysozyme and snailase than was that of the wild‐type strain.…”
Section: Discussionmentioning
confidence: 98%
“…In S . cerevisiae , low ergosterol level caused sensitivity to paraquat-induced oxidative stress 56 , 57 . In fact, membrane permeability plays important role in the adaptation to oxidative stress and the altered sterol production may result in higher sensitivity to inducers of oxidative stress 58 60 .…”
Section: Discussionmentioning
confidence: 99%